Interlinked relationship between e-cigarette use and physical activity behaviour among Malaysian university students who use e-cigarettes: A cross-sectional study - Chrisminder Dain; Lei Hum Wee; Yin How Wong; Yin Yin Ooi; Ching Sin Siau; Suzanna Awang Bono (PLoS ONE, 2026)
Introduction E-cigarette (EC) use is increasing among young adults in Malaysia. However, evidence on how EC-related behaviours and perceived physical activity barriers are associated with physical activity participation remains limited. This study examined the associations between EC-related behaviours and perceived physical activity barriers with physical activity status among Malaysian university students who use EC. Methods A cross-sectional online survey was conducted between December 2023 and July 2024 across six Malaysian universities. Of 660 respondents, 564 met the age and International Physical Activity Questionnaire (IPAQ) criteria and were included in the analysis. Physical activity was classified as active and inactive. Exposures included EC use frequency, dual use, nicotine content, nicotine dependence, EC knowledge, motivations and perceptions for EC use, EC-related side effects, and perceived physical activity barrier items across personal, social and physical domains. Associations were analysed using chi-square tests and binary logistic regression, with odds ratios (ORs) and 95% confidence intervals. Results Overall, 64.9% were classified as active. At the crude level, EC use frequency, nicotine content, and dual-use status were associated with physical activity. However, these variables were not retained in the multivariable model due to multicollinearity. Nicotine dependence emerged as one of the strongest behavioural correlates of physical inactivity, with higher dependence associated with greater odds of physical inactivity. Perceived barriers to physical activity, particularly personal and social barriers, demonstrated the strongest and most consistent associations, with substantially higher odds of inactivity across barrier levels. EC knowledge and perception variables were not independently associated after adjustment, although item-level patterns were observed. Reported EC related symptoms were mainly gastrointestinal, respiratory, and neurological but were not analysed in relation to physical activity. Conclusion Physical activity among Malaysian university students who use EC is more consistently associated with nicotine dependence and perceived barriers, than with sociodemographic or knowledge variables. These findings suggest that interventions may benefit from addressing behavioural dependence and contextual constraints. Given the cross-sectional design, these results should be interpreted as hypothesis-generating. Implications Physical activity among university students who use EC appears more closely associated with nicotine dependence and perceived barriers than with knowledge or sociodemographic factors. While some EC use patterns showed crude associations, nicotine dependence emerged as one of the strongest behavioural correlates of physical inactivity. Lower perceived barriers, particularly personal and social, were consistently linked to higher activity participation. These findings suggest that intervention strategies may benefit from addressing behavioural dependence alongside reducing personal and social barriers to physical activity, particularly factors related to motivation, self-confidence, and competing demands. Integrating accessible, context-specific physical activity opportunities within EC cessation or harm-reduction programmes may enhance engagement and promote healthier lifestyle behaviours among young adults.